Improving the Chemical Quality of Compost from Bioconversion of Multi Types of Organic Waste Using Black Soldier Fly Larvae and EM-4 - Indriyani Indriyani; Refi Arioen; Ari Beni Santoso; Zaenal Arifin; Purnama Edy Santosa (Postgraduate, University of Mataram, 2023)
Waste that is not handled properly will have a negative impact on the quality of the environment in society. Organic waste is the main problem that is often faced by Indonesian people. Waste management using the bioconversion method with the help of Black soldier Fly (BSF) larvae and EM-4 bioactivators can reduce waste capacity and benefit the community. This study aims to compare the ability of bioconversion agents and the quality of various types of organic waste used for bioconversion. This study used a factorial randomized block design with 2 factors. The first factor was a bioconversion agent consisting of 3 levels, P0 (control), P1 (EM-4 activator) (15 ml), P2 (Black Soldier Fly) (5 gram/bio-pond). The second factor is the type of organic waste which consists of 3 levels, namely L1 (pineapple peel waste), L2 (orange peel waste) and L3 (bagasse). The results showed that BSF larvae have the potential as bioconversion agents and their ability to approach EM-4. In general, the application of bioconverting agents improves the quality of compost compared to that without the application of bioconverting agents. The application of a bioconversion agent combined with pineapple peel waste has a quality close to the standard of Minister of Agriculture No. 261 of 2019